Private Water Projects - Izaguirre, Ada Karina (World Bank, Washington, DC, 2012)
Drawing on the World Bank's Private Participation in Infrastructure Project Database, this Note reviews developments in the water and sewerage sector of developing countries in 2004 and changes in private participation in the sector since 2001. Data for 2004 show that total investment in water and sewerage projects with private participation amounted to nearly US$2 billion. Recent private activity in water was concentrated in a few countries and focused on treatment plants and smaller projects.